Effect of Moldavian dragonhead (Dracocephalum moldavica L.) leaves on the baking properties of wheat flour and quality of bread - Dariusz Dziki; Grażyna Cacak-Pietrzak; Urszula Gawlik-Dziki; Alicja Sułek; Sławomir Kocira; Beata Biernacka (CyTA - Journal of Food, 2019)
The dried and powdered leaves of Moldavian dragonhead (Dracocephalum moldavica L.) (0, 1, 3, 4, and 5 g/100 g of wheat flour) were added to the wheat flour to make bread. Farinograph properties of dough were studied, and the properties of enriched bread were evaluated. According to the results, Moldavian dragonhead leaves increased water absorption by the flour but decreased the volume of bread and crumb lightness. The enriched breads were characterized by a higher value of crumb hardness than that of control bread. The total phenolics content linearly increased with the percentage increase in the addition of dragonhead leaves from 4.8 to 10.1 mg GAE/g dry mass. As a result, the antioxidant activity of bread increased. Sensory evaluation revealed that the wheat bread can be supplemented with Moldavian dragonhead leaves up to 3 g/100 g wheat flour addition of dragonhead leaves with good consumer acceptability.